2017
DOI: 10.1108/yc-05-2017-00699
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of consumer lifestyles on ecological behavior among young Indian consumers

Abstract: Purpose The purpose of this paper is to identify what lifestyles best explain and impact ecological behavior among young Indian consumers. Design/methodology/approach This paper adapts the lifestyle scale developed by He et al. (2010) and the Actual Commitment scale to the Indian context to describe its impact on the young consumer’s ecological profile. The study is based on an extensive literature review. The data were obtained from a questionnaire handed out to a sample of 250 students. With the informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 138 publications
8
62
0
Order By: Relevance
“…Related to this finding, we mention Adnan et al's [62] study that investigates the young ecological market segment. Researchers' findings explain that these people are constantly taking challenging actions, are always trying to improve themselves, and have pro-ecological behaviour.…”
Section: Discussionmentioning
confidence: 65%
“…Related to this finding, we mention Adnan et al's [62] study that investigates the young ecological market segment. Researchers' findings explain that these people are constantly taking challenging actions, are always trying to improve themselves, and have pro-ecological behaviour.…”
Section: Discussionmentioning
confidence: 65%
“…Accordingly, Palan and Mallalieu's () research on teen consumers revealed that the young consumers do not like if they are ignored by the marketer. As a result, Gil, Kwon, Good, and Johnson () and Adnan, Ahmad, and Khan () highlighted the importance of investigating the youth market. Surprisingly, despite the importance of this young consumer market, there is sparse research on the consumer behavior of young people (Adnan et al, ; Gentina & Muratore, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, Palan and Mallalieu's (2012) research on teen consumers revealed that the young consumers do not like if they are ignored by the marketer. As a result, Gil, Kwon, Good, and Johnson (2012) and Adnan, Ahmad, and Khan (2017) highlighted the importance of investigating the youth market.…”
Section: Significance Of Young Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature Review. As research shows, consumer behaviour is influenced by subjects such as lifestyle (Adnan et al, 2017), cultural differences and the place of residence (Zhong et al, 2018), opinion and experience of those around them (Jain et al, 2018), individual's hobbies and free-time activities (Silveira et al, 2018), emotions, experiences and other psychological motives, external factors ) and many more. Consumer decision-making process is complex and complicated as during it the individuals are affected by intrinsic and extrinsic factors (Nash, 2018).…”
mentioning
confidence: 99%